Grimm’s reformatory: case no. 442, code name: Libra - Sullivan, Sarah Joyce (Kansas State University, 2010)
This thesis stands as the first part of the earliest novel in a series that will appeal to the mass public, utilizing well-celebrated fairy tale elements and introducing old elements of courtly romance from the medieval literature period. In doing so, I have worked to create a fantastical world with obvious parallels to historical and present notions of society, culture, and human interactions, but with a new and interesting twist on concepts readers are familiar with. The universe I’ve created is able to be introduced in this first installment and gradually broadened as the series progresses to prevent exhaustive detail which may distract the reader. Also, it is restricted by specific laws in terms of magical abilities and power in order to give the reader boundaries to react within and prevent the unhelpful limitlessness that causes a loss of interest. The main character, Emily Fenhorn, is a thirteen-year-old girl who is fairly average in her adolescence. She’s neither the weakest nor the strongest character, leaving room for both growth and human frailty. The conflicts that affect Emily in this first installment center primarily on problems that teenagers deal with on a regular basis such as the need for acceptance, making new friends, making and dealing with enemies, popularity, and academic concerns. Unlike other thirteen-year-olds, Emily is plagued by a horrifying ‘gift’ that she doesn’t know how to control; a gift which ends up earning her place at Grimm’s Reformatory.
Keywords: Grimm; Fairy; Fantasy; Folklore; Folklore (0358)